IDENTIFICACIÓN DE LAS CONDICIONES ERGONÓMICAS, AMBIENTALES, ORGANIZACIONALES DE PUESTOS DE TRABAJO PARA USUARIAS DE VIDEOTERMINALES DEL ÁREA ADMINISTRATIVA EN UNA INSTITUCIÓN - ALDO PIÑEDA GERALDO; YURANI NATALI BLANCO CARDONA (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2019)
The existing risk factors are related to the exposure of the activities carried out in the administrative area. Among thosethat stand out: biomechanics, environmental, organizational, psychosocial and safety conditions. According to thedangers that were evident in the administrative area, the main dangers were: prolonged sitting postures, forced postures,repetitive movements in the upper limbs (due to fingering tasks), overexertion: hyperextension of the upper and lowerlimbs and flexion of the trunk. On the other hand, inadequate designs of the jobs in the administrative area wereobserved.